Taxonomic and geographic novelties of Acarnus (Porifera: Demospongiae) from the Brazilian coast, with description of two new species - Ozga, Aline Vasum; Santos, George Garcia; Menegola, Carla (Zootaxa, 2024)
Acarnus are poecilosclerid sponges characterized mainly by cladotylote megascleres. Five species are known on the Brazilian coast: Acarnus innominatus Gray 1867, Acarnus radovani (Boury-Esnault, 1973), Acarnus toxeata Boury-Esnault, 1973, Acarnus nicoleae van Soest, Hooper & Hiemstra, 1991 and Acarnus microxeatus Nascimento & Pinheiro, 2023. This study describes two new Brazilian species, Acarnus hooperi sp. nov. and Acarnus tupiniquim sp. nov., from Rio de Janeiro and Bahia States, respectively, whose diagnosis is the presence of tylostyles, a character formally recorded for the first time in the family Acarnidae and the genus Acarnus. We also describe two of the previously known species, A. innominatus and A. toxeata. Additionally, an identification key for the Acarnus species from the Tropical Western Atlantic is proposed.